2009
DOI: 10.1016/j.memsci.2009.02.020
|View full text |Cite
|
Sign up to set email alerts
|

Removal of boron, fluoride and nitrate by electrodialysis in the presence of organic matter

Abstract: 14The removal of the trace inorganic contaminants boron (B(OH)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
77
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 198 publications
(79 citation statements)
references
References 43 publications
2
77
0
Order By: Relevance
“…This is because the spacing of the (200) plane was reduced by the photocatalytic reduction from NO3 − to NO2 − , the ionic radii of which were ca. 0.20 and 0.16 nm, respectively [21,22]. The island-like deposits as seen in the SEM image ( Fig.…”
Section: Microscopic Morphology Of the Sample Surfacementioning
confidence: 90%
“…This is because the spacing of the (200) plane was reduced by the photocatalytic reduction from NO3 − to NO2 − , the ionic radii of which were ca. 0.20 and 0.16 nm, respectively [21,22]. The island-like deposits as seen in the SEM image ( Fig.…”
Section: Microscopic Morphology Of the Sample Surfacementioning
confidence: 90%
“…In general, high removals of metals are achieved by this process although membrane type affects metal removal [46,134,8,130,9]. Metal speciation plays an important role.…”
Section: Electrodialysismentioning
confidence: 99%
“…It has been observed that humic acid particles, which are negatively charged in neutral pH, can be responsible for fouling phenomenon during electrodialysis. Usually, organic matter particles are predominantly deposited on anion-exchange membranes [17].…”
Section: Introductionmentioning
confidence: 99%
“…al [17] did research into fluoride removal with the use of ED in the presence of organic matter. They examined the influence of various organic matter substances (humic acids, HAs; tannic acids, TAs; alginic acid, AAs) on defluoridation efficiency.…”
Section: Introductionmentioning
confidence: 99%